Preparation of Nitrogen-Doped Carbon Materials from Monosodium Glutamate and Application in Reduction of p-Nitrophenol - Ke-ying Cai; Ying Mei Zhou; Peng Wang; Huan Li; Yan Li; Wei Tao (Bulletin of Chemical Reaction Engineering & Catalysis, 2018)
Nitrogen-doped carbons (NCs) as supports for metal catalysts used in heterogeneous reactions are increasingly being investigated. In this work, NCs were prepared from monosodium glutamate (MSG) by direct carbonization, which were used as supporters to prepare Bi/NC catalysts. The Bi/NC catalysts were characterized by X-ray powder diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscope (TEM), and nitrogen adsorption isotherm. The results indicate that nitrogen was doped in the formation of pyridinic N, pyrrolic N, and graphitic N. The NCs possess high surface area (~652 m2/g) and uniform mesopore size (~2.11 nm). Bismuth nanoparticles (NPs) dispersed uniformly in NC with diameter of 10-20 nm. The catalytic performances were investigated using the reduction of 4-nitrophenol (4-NP) with excess potassium borohydride as a model reaction, the results indicating that the Bi/NC catalysts have higher activity and better reusability than the Bi/AC catalyst. Under the following conditions: 100 mL of 4-NP (2 mM), 0.03 g of 3%Bi/NC, n(KBH4) : n(4-NP) = 40:1, and at room temperature, the rate constant k can reach 0.31 min-1.